Spontaneous hot flow anomalies at Mars and Venus. Issue 10 (6th October 2017) - Collinson, Glyn; Sibeck, David; Omidi, Nick; Grebowsky, Joseph; Halekas, Jasper; Mitchell, David; Espley, Jared; Zhang, Tielong; Persson, Moa; Futaana, Yoshifumi; Jakosky, Bruce
Abstract: We report the first observations of Spontaneous Hot Flow Anomalies (SHFAs) at Venus and Mars, demonstrating their existence in the foreshocks of other planets beyond Earth. Using data from the ESA Venus Express and the NASA Mars Atmosphere and Volatile EvolutioN (MAVEN) spacecraft, we present magnetic and plasma observations from events at both planets, exhibiting properties similar to "classical" Hot Flow Anomalies, with bounding shock‐like compressive regions and a hot and diffuse core. However, these explosive foreshock transients were observed without any attendant interplanetary magnetic field discontinuity, consistent with SHFAs observed at Earth and our hybrid simulations. Key Points: We report the first extraterrestrial observations of Spontaneous Hot Flow Anomalies (SHFAs) in the foreshocks of Venus and Mars Although occurring at different planets, the events were very similar in duration and character SHFAs have the capability to directly impart energy into the ionospheres of unmagnetized planets